The Influence of Language on Spatial Reasoning: Reading Habits Modulate the Formulation of Conclusions and the Integration of Premises - Castelain, Thomas; Van der Henst, Jean-Baptiste (Frontiers in Psychology, 2021)
In the present study, we explore how reading habits (e.g. reading from left-to-right in French or reading from right-to-left in Arabic) influence the scanning and the construction of mental models in spatial reasoning. For instance, when participants are given a problem like A is to the left of B; B is to the left of C; What is the relation between A and C? They are assumed to construct the model: A B C. If reading habits influence the scanning process, then readers of French should inspect models from left-to-right whereas readers of Arabic should inspect them from right-to-left. The prediction following from this analysis is that readers of French should be more inclined to produce ‘left’ conclusions (i.e. A is to the left of C) whereas readers of Arabic should be more inclined to produce ‘right’ conclusions (i.e. C is to the right of A). Furthermore, one may expect that readers of French show a greater ease in constructing models following a left-to-right direction than models following a right-to-left direction, while an opposite pattern might be expected for readers of Arabic. We tested these predictions in two experiments involving French and Yemeni participants. Experiment 1 investigated the formulation of conclusions from spatial premises and Experiment 2, which was based on non-linguistic stimuli, examined the time required to construct mental models from left-to-right and from right-to-left. Our results show clear differences between the two groups. As expected, the French sample showed a strong left-to-right bias, but the Yemeni sample did not show the reverse bias. Results are discussed in terms of cultural influences and universal mechanisms.